2020
DOI: 10.1111/1750-3841.15186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary choline, betaine, and L‐carnitine on the generation of trimethylamine‐N‐oxide in healthy mice

Abstract: Trimethylamine‐N‐oxide (TMAO) is considered to have negative effect on human health. Different precursors of TMAO, such as choline, betaine, and L‐carnitine, are commonly found in daily foods. The aim of the present study was to compare the ability of different precursors to be metabolized into TMAO, as well as the possible effect of chronic administration with TMAO precursors on TMAO production. The rate of TMAO generation after single gavage with different precursors was L‐carnitine > choline >betaine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…Since plasma TMAO levels are highly correlated with dietary patterns and the nutritional composition of foods [ 17 , 18 ], dietary intervention may be an alternative strategy for inhibiting TMAO production [ 19 ]. A methionine-restricted (MR) diet has emerged as a highly preferable dietary intervention strategy since it is reported to exert many beneficial effects including the promotion of vascular health [ 20 ], reduction in fat deposition [ 21 ], improvement of glucose homeostasis [ 22 ], improving oxidative stress and inflammation [ 23 , 24 ], and a prolonged life span [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since plasma TMAO levels are highly correlated with dietary patterns and the nutritional composition of foods [ 17 , 18 ], dietary intervention may be an alternative strategy for inhibiting TMAO production [ 19 ]. A methionine-restricted (MR) diet has emerged as a highly preferable dietary intervention strategy since it is reported to exert many beneficial effects including the promotion of vascular health [ 20 ], reduction in fat deposition [ 21 ], improvement of glucose homeostasis [ 22 ], improving oxidative stress and inflammation [ 23 , 24 ], and a prolonged life span [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by demonstrated that the rate of TMAO generation after single gavage with different precursors is L-carnitine > choline > betaine; However, long-term dietary intervention showed that the production for TMAO in chronic choline-treated group is 2.8 and 1.6 times than that in L-carnitine and betaine groups, respectively (Yu et al, 2020). Priscilla and colleagues also investigated TMA production from dietary precursors in an in-vitro model of the human colon, they found that the rate of TMA production from precursors is choline > L-carnitine > betaine > γ-butyrobetaine, and conversion of L-carnitine to TMA is slower than that of choline (Day-Walsh et al, 2021).…”
Section: The Source Of Tmaomentioning
confidence: 98%
“…The levels of TMAO and TMA in serum were measured according to the previous methods by liquid chromatography with tandem mass spectrometry (LCMS/MS). 16…”
Section: Serum Tmao and Trimethylamine (Tma) Quantificationmentioning
confidence: 99%